INTERNATIONAL LEGAL REGULATION OF THE PROTECTION OF JOURNALISTS’ RIGHTS DURING ARMED CONFLICTS (International journal of artificial intelligence, 2025)
This article explores the international legal framework for protecting journalists’ rights in armed conflict zones. It examines the application of international humanitarian law (IHL), human rights law, and media regulations to ensure the safety and professional integrity of journalists. The study highlights the increasing risks journalists face, including targeted killings, arbitrary arrests, and enforced disappearances, as well as the ongoing issue of impunity for crimes against media workers. Special attention is given to the role of international organizations, such as UNESCO and the ICRC, in safeguarding press freedom and enforcing legal protections. The article also analyzes the debate surrounding the legal status of journalists in conflict zones, comparing the protection afforded to war correspondents and independent reporters under the Geneva Conventions and their Additional Protocols. Lastly, it discusses the necessity of accreditation and the challenges in establishing a universally recognized legal status for journalists in contemporary warfare.